Nonglacial rapid climate events: Past and future - Overpeck, Jonathan (The National Academy of Sciences, 2000)
The paleoclimate record makes it clear that rapid climate shifts of the 20th century are only a subset of possible climate system behavior that might occur in the absence of glacial conditions, and that climatic surprises could be a challenge for society even in the absence of significant greenhouse warming.